Goldilocks and the three bears - Mitchelhill, Barbara; Mathers, Michelle (London : Collins, 2005)
Daddy bear, Mummy Bear and baby bear went for a walk. When they came back they had a big surprise.
K-3.
Keywords: Bears -- Fiction; Reading training, English (Elementary).; Stories without words